2007
DOI: 10.1577/m06-187.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Relative Volume on Radio Transmitter Expulsion in Subadult Common Carp

Abstract: Expulsion of surgically implanted radio transmitters is a problem in some fish telemetry studies. We conducted a 109-d experiment to test the hypothesis that variation in relative volume of transmitters surgically implanted in subadult common carp Cyprinus carpio would affect transmitter expulsion. We also necropsied fish at the end of the experiment to evaluate histological evidence for the mechanism of expulsion. Survival rate was high during our experiment; all control fish and 88% of the fish subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…The experimental period was during the transition from a period of active feeding to a more inactive overwintering period, the seasonal water parameter variation may affect the growth of bighead carp after surgery. Our results were similar to a common carp study which showed that relatively low temperature and feeding rate were the main reasons for the decrease in growth after transmitters were surgically implanted in fish (Penne et al 2007). The decrease in growth for the control group 56 days after surgery might also be attributed to the seasonal water parameter variations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The experimental period was during the transition from a period of active feeding to a more inactive overwintering period, the seasonal water parameter variation may affect the growth of bighead carp after surgery. Our results were similar to a common carp study which showed that relatively low temperature and feeding rate were the main reasons for the decrease in growth after transmitters were surgically implanted in fish (Penne et al 2007). The decrease in growth for the control group 56 days after surgery might also be attributed to the seasonal water parameter variations.…”
Section: Discussionsupporting
confidence: 91%
“…Still others believe that the size of the transmitters and their adhesion should be considered. Larger transmitters encapsulated in a fibrous capsule might enhance the adhesion rate with the intestinal body wall or intestinal tract and help transmitters stay in the body, while smaller transmitters might wear the body wall or intestinal tract due to less tissue adhesion, causing expulsion of the transmitters though the worn channel (Penne et al 2007). In the current study, it was difficult to judge retention or expulsion of transmitters was affected based only on the existence of fibrous capsule tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This encapsulation protected the transmitter, preventing tag expulsion through the incision site or transintestinal expulsion. In fact, the rapid encapsulation of the transmitter has been shown to play a role in retention by limiting its mobility and minimizing the risk of organ damage (Thoreau & Baras, 1997;Penne et al, 2007;Luo et al, 2015). Additionally, the effect of encapsulation processes and incision site on wound healing and tag retention should also be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…To alleviate or suppress such complications, several studies have investigated the factors associated with the adverse effects from surgical tagging, including type of anesthetic used for anesthesia and immobilization (King et al, 2005;Carter, 2011;Vandergoot et al, 2011;Javahery et al, 2012;Trushenski et al, 2012;Kanani, 2013), transmitter type and size and its relationship with fish size (Penne et al, 2007;Thorstad et al, 2009), surgeon experience (Smith et al, 2009;Brown et al, 2011;Cooke et al, 2011b), as well as sterilization of transmitters and surgical instruments, attachment methods, incision type and location, and suture material and pattern (Cooke et al, 2003;Wagner et al, 2011;Brown et al, 2013).…”
Section: Introductionmentioning
confidence: 99%